The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1051/0004-6361:20010226
|View full text |Cite
|
Sign up to set email alerts
|

Slow magnetoacoustic waves in coronal loops: EIT and TRACE

Abstract: Abstract. On May 13, 1998 the EIT (Extreme ultraviolet Imaging Telescope) on board of SoHO (Solar and Heliospheric Observatory) and TRACE (Transition Region And Coronal Explorer) instruments produced simultaneous high cadence image sequences of the same active region (AR 8218). TRACE achieved a 25 s cadence in the Fe ix (171Å) bandpass while EIT achieved a 15 s cadence (operating in "shutterless mode", SoHO JOP 80) in the Fe xii (195Å) bandpass. These high cadence observations in two complementary wavelengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
113
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 28 publications
13
113
1
Order By: Relevance
“…Also, the apparent propagation speed appears constant at these distances. It is consistent with previous observations of this phenomenon, which showed that any noticeable speed variation can appear at larger heights only (Robbrecht et al 2001;Gupta et al 2010). No other periodicities, except 3-min oscillations, are found in the power spectrum of the time signal.…”
Section: The Measurement Of the Apparent Phase Speedsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, the apparent propagation speed appears constant at these distances. It is consistent with previous observations of this phenomenon, which showed that any noticeable speed variation can appear at larger heights only (Robbrecht et al 2001;Gupta et al 2010). No other periodicities, except 3-min oscillations, are found in the power spectrum of the time signal.…”
Section: The Measurement Of the Apparent Phase Speedsupporting
confidence: 93%
“…The spread of the measured speeds is usually attributed to the variation of the angle between the propagating direction and image plane in different cases. Robbrecht et al (2001) reported that the phase speeds of propagating disturbances measured in TRACE 171 Å (1 MK) are normally lower than those measured in EIT 195 Å (1.6 MK). The temperature-dependence of the phase speed was recently found in polar plumes and the interplume medium with AIA (Krishna Prasad et al 2011).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nakariakov and Ofman (2001) estimated the magnetic field strength in an oscillating loop to be ≈1.3 mT. Slow magnetoacoustic disturbances propagating with speeds of roughly 100 km s −1 have been observed by the EIT and TRACE instruments in active-region loops (Robbrecht et al 2001).…”
Section: Coronal Oscillations and Wavesmentioning
confidence: 99%
“…Doschek et al (2008) also used EIS observations to investigate strong blueshifts at the periphery of an AR, which might contribute significantly to the solar wind. On the other hand, the propagation of an intensity disturbance may be explained as a slow magnetoacoustic wave, since the inferred speed is close to or below the coronal sound speed (Robbrecht et al 2001). But the phase speed reported in Robbrecht et al (2001) is the projected speed component rather than the true phase speed, which may exceed the coronal sound speed.…”
Section: Introductionmentioning
confidence: 98%